Tea Polyphenols Enhanced the Antioxidant Capacity and Induced Hsps to Relieve Heat Stress Injury. (9th August 2021) - Yin, Bin; Lian, Ruirui; Li, Zhen; Liu, Yueyue; Yang, Shifa; Huang, Zhongli; Zhao, Zengcheng; Li, Ying; Sun, Chuanxi; Lin, Shuqian; Wan, Renzhong; Li, Guiming
Abstract : Keap1-Nrf2-ARE and heat shock proteins (Hsps) are important endogenous protection mechanisms initiated by heat stress to play a double protective role for cell adaptation and survival. H9C2 cells and 80 300-day-old specific pathogen-free chickens were randomly divided into the control and tea polyphenol groups and used to establish a heat stress model in vitro and in vivo. This task was conducted to explore the protection and mechanism of tea polyphenols in relieving thermal injury. A supplement with 10  μ g/mL tea polyphenols could effectively relieve the heat damage of H9C2 cells at 42°C. Accordingly, weaker granular degeneration, vacuolar degeneration, and nucleus deep staining were shown. A strong antioxidant capacity was manifested in the upregulation of the total antioxidant capacity (T-AOC) (at 5 h, P < 0.05 ), Hemeoxygenase-1 mRNA (at 2 h, P < 0.01 ), superoxide dismutase (SOD) (at 2, 3, and 5 h, P < 0.05 ), and Nrf2 (at 0 and 5 h, P < 0.01 ). A high expression of Hsps was reflected in CRYAB at 3 h; Hsp27 at 0, 2, and 3 h (P < 0.01 ); and Hsp70 at 3 and 5 h (P < 0.01 ). The supplement with 0.2 g/L tea polyphenols in the drinking water also had a good effect in alleviating the heat stress damage of the myocardial cells of hens at 38°C. Accordingly, light pathological lesions and downregulation of the myocardial injury-related indicators (LDH, CK, CK-MB, and TNF- α ) were shown. The mechanism was related to the upregulation of T-AOC (at 0 h, P < 0.05 ), GSH-PX (at 0.5 d, P < 0.01 ), SOD (at 0.5 d), and Nrf2 (at 0 d with P < 0.01 and 2 d with P < 0.05 ) and the induced expression of CRYAB (at 0.5 and 2 d), Hsp27 (at 0, 0.5, and 5 d), and Hsp70 (at 0 and 0.5 d). In conclusion, the tea polyphenols enhanced the antioxidant capacity and induced Hsps to relieve heat stress injury.